Medieval badges : their wearers and their worlds - Rasmussen, Ann Marie (Middle Ages series., 2021)
Mass produced of tin-lead alloys and cheap to purchase, medieval badges were brooch-like objects displaying familiar images. Sumptuously illustrated, Medieval Badges considers all badges, whether they originated in religious or secular contexts, and highlights the ways in which badges could confer meaning and identity on their wearers.